The Beta Subunit of Non-bifurcating NADH-Dependent [FeFe]-Hydrogenases Differs From Those of Multimeric Electron-Bifurcating [FeFe]-Hydrogenases - Losey, Nathaniel A.; Poudel, Saroj; Boyd, Eric S.; McInerney, Michael J. (Frontiers in Microbiology, 2020)
A non-bifurcating NADH-dependent, dimeric [FeFe]-hydrogenase (HydAB) from Syntrophus aciditrophicus was heterologously produced in Escherichia coli, purified and characterized. Purified recombinant HydAB catalyzed NAD+ reduction coupled to hydrogen oxidation and produced hydrogen from NADH without the involvement of ferredoxin. Hydrogen partial pressures (2.2 to 40.2 pascals) produced by the purified recombinant HydAB at NADH to NAD+ ratios of 1 to 5 were similar to the hydrogen partial pressures generated by pure and cocultures of S. aciditrophicus (5.9 to 36.6 Pa). Thus, the hydrogen partial pressures observed in metabolizing cultures and cocultures of S. aciditrophicus can be generated by HydAB if S. aciditrophicus maintains NADH to NAD+ ratios greater than one. The flavin-containing beta subunits from S. aciditrophicus HydAB and the non-bifurcating NADH-dependent S. wolfei Hyd1ABC share a number of conserved residues with the flavin-containing beta subunits from non-bifurcating NADH-dependent enzymes such as NADH:quinone oxidoreductases and formate dehydrogenases. A number of differences were observed between sequences of non-bifurcating NADH-dependent enzymes and [FeFe]-hydrogenases and formate dehydrogenases known to catalyze electron bifurcation including differences in the number of [Fe-S] centers and in conserved residues near predicted cofactor binding sites. These differences can be used to distinguish members of these two groups of enzymes and may be relevant to the differences in ferredoxin-dependence and ability to mediate electron-bifurcation. These results show that two phylogenetically distinct syntrophic fatty acid-oxidizing bacteria, Syntrophomonas wolfei a member of the phylum Firmicutes, and S. aciditrophicus, a member of the class Deltaproteobacteria, possess functionally similar [FeFe]-hydrogenases that produce hydrogen from NADH during syntrophic fatty acid oxidation without the involvement of reduced ferredoxin. The reliance on a non-bifurcating NADH-dependent [FeFe]-hydrogenases may explain the obligate requirement that many syntrophic metabolizers have for a hydrogen-using partner microorganism when grown on fatty, aromatic and alicyclic acids.